Pedagogical practices and training in higher education with technological field: a case study in an institution located in the interior of the state of São Paulo, BR - Queiroz, Shara da Silva; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2023)
There is a technological revolution underway that will transform, above all, the way in which information is operated and transmitted. This research identifies facilities and difficulties of higher education professors at a higher education institution in science and technology, referring to active methodologies and technologies for use in the classroom. The objective is to present proposals for improvement/qualification of competences, for new technologies, adequate to the new requirements demanded by the educational institution. The approach is qualitative and the technical procedure is the case study. The results obtained based on the practical experience of professionals with individual technological knowledge and skills, based on the literature, show that there is considerable mastery and clarity. However, customized training is required to use specific technologies for disciplines among the courses offered. The contribution of this work is to present proposals for improvements, being the use of: (i) digital tools – Quizizz, Kahoot, Pear Deck Mentimeter, Trello, Miro, Mural, Mindmeister, Padlet, Jamboard, Symbaloo, Edmodo Blackboard, Notion, Piktochart, Visme, etc; (ii) active methodologies – learning between teams; less use was identified of some that they know and others that they do not use, such as: Socratic Seminar, Gamification, Inverted Classroom and Hybrid Teaching; (iii) Digital skills – improve skills on digital tools.
Keywords: Active methodologies; digital skills and tool